Hydrocarbon Separation: Designer Metal–Organic Frameworks for Size‐Exclusion‐Based Hydrocarbon Separations: Progress and Challenges (Adv. Mater. 44/2020). Issue 44 (3rd November 2020) - Wang, Hao; Liu, Yunling; Li, Jing
Abstract : Highly selective and cost‐effective separation of light hydrocarbons is of vital importance for the petrochemical industry. In light of their tunable porosity and functionality, metal–organic frameworks (MOFs) hold great promise for the adsorptive separation of hydrocarbons with high similarity. Tailored MOFs with optimal pore size and shape can be achieved for the most efficient separation of light hydrocarbons through molecular sieving, as reviewed by Jing Li and co‐workers in article number 2002603 .